Reparation for Service Failure Through Service Recovery: An Assessment of Consumer Behaviour in an Online Shopping Context - Mazhar, Muhammad; Nadeem, Muhammad Amir; Abbasi, Haider Ali; Tariq, Umaima; Jan, Amin; Jaffar, Rao Abdul Hannan (Business Management and Strategy, 2022)
A service failure in online shopping exacerbates customers’ behaviour towards a brand/webstore. However, service recovery is deemed an instrumental factor to atone for the customer loss after a service failure. To examine this, the current study aims to analyse the relationship between service failure and its downstream effect on the future customer behavioural intentions (i.e., customers’ switching and repurchase. Moreover, this study incorporates the mediating role of service recovery between service failure and customers’ future intentions. The survey technique was employed to achieve objectives by collecting data from 364 Malaysian customers who purchased from any webstore in the last six months. Data was analysed through SPSS 24.0 and SEM-PLS 3.3.3. The results of the study revealed that service recovery has a positive impact on repurchase intention and switching intention. Furthermore, it is observed that due to cultural influences, the effect of service recovery on repurchase intention is less significant as compared to switching intention, which shows that in a specific culture, service recovery is less important than social loss. The practical implications of the study are two-fold. Firstly, the service provider should consider customers’ expectations regarding service recovery. Secondly, service providers should not be limited to financial compensation only; instead, they should include non-financial compensation to retain customers from a specific culture.